Identification of genes in response to cucurbit aphid-borne yellows virus infection in melon - YANG Siyu; GONG Zihui; HU Zhongyuan; ZHANG Mingfang; YANG Jinghua (浙江大学学报. 农业与生命科学版)
Cucurbit aphid-borne yellows virus (CABYV) is one of the most important viruses infecting cucurbits, such as melon (Cucumis melo), and severely affects the yield and quality of crops. Identification of CABYV-responsive genes can provide target genes for breeding of melon resistant to the viral disease. In this study, we used the CABYV infectious cloning vector to inoculate the melon XZM, and the disease identification and transcriptome analysis in the melon XZM after CABYV inoculation were performed at 0 dpi (days post inoculation), 5 dpi, 10 dpi, 15 dpi and 20 dpi. The results indicated that melon leaves showed typical disease symptoms of leaf chlorosis, yellowing and leaf thickening at 20 dpi. A total of 1 654 differentially expressed genes (DEGs) in response to CABYV infection were identified by transcriptome sequencing analysis, including 677 up-regulated genes and 977 down-regulated genes. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses showed that the responsive genes were mainly enriched in plant-pathogen interaction, photosynthesis, starch and sucrose metabolism, glyoxylate and dicarboxylate metabolism, etc., pathways and processes. Co-expression and interaction analysis of DEGs revealed that RIN4, a key gene in pathogen defense responses, may negatively regulate responses to CABYV infection in melon. This study demonstrates the possible molecular mechanism of responses to CABYV infection and provides a basis for breading melon against CABYV.